FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENGURUS PADA KOPERASI UNIT DESA (KUD) BUMI ASIH KABUPATEN ROKAN HULU - Dehotman, Khornelis (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The purpose of this study was to determine the factors that influence the performance of the management of the Bumi Asih Koperasi Unit Desa (KUD) in Rokan Hulu Regency. The population used in this study were all cooperative managers totaling 30 people. Thus the sample of this study is 30 cooperative managers. The data analysis method used is descriptive and quantitative. The regression results obtained that can be seen in fact that the three variables (X) are the factors of education and training variables (X1) 1.334 <2.052, not significant for the variable (Y). Factor variable employee welfare 2,393> 2,052 significant to variable (Y) and Motivation Factor variable 0,272 <2,052. not significant to variable (Y). Viewed from the results of linear regression that the determinant coefficient value (R-Square) is 0.346 or 34.6%. This means that simultaneously the influence of variable factors of education and training (X1), variable factors of employee welfare (X2) and variables Factors of motivation (X3) on Y performance is 34.6% and the remaining 65.4 is influenced by variables not examined